Form Design of Professional Training of the Future Primary School Teachers Based on Constructivist Pedagogy - Yaroshynska, Olena (Pedagogical Discourse, 2016)
The expediency of constructivist pedagogy ideas application at the stage of creation the project of the innovative educational environment of future teachers’ professional training is explained in the article. The system of the main principles of constructivist didactics in the context of professional training of the future primary teachers is highlighted. Taking into consideration modern psychological and pedagogical research and own teaching experience, the peculiarities of realization the methods of form projecting of future primary teachers professional training based on constructivist pedagogy are presented. The following algorithm of projecting actions was suggested: diagnosis of existing forms of training efficacy → change forecasting → definition characteristics of the forms that ensure achieving the intended effect → images generalization of future professional training forms and their specification → development of the technological aspects of their implementation. Some forms of future primary school teachers professional training in terms of designing the educational environment (educational component) were determined, such as: lecture (problematic, binary, lecture-visualization, pre-planned errors lecture with pre-planned errors, lecture-conference etc.), interactive lecture of subject-to-subject interaction (lecture with pauses, guided lecture, lecture with the help of students); practical, laboratory practice-oriented classes; seminars (discussion club, debate etc. etc.) independent work; individual work on the system of personalized teaching «the Keller Plan»; educational projects (term papers, qualification papers). The expediency of their choice was explained and characterized in the context of the tasks realization – creation of innovative educational environment project of future primary teachers’ professional training. Recommendations for the teachers concerning their usage in the practical work of higher professional school were given. Key words: design of the educational environment, forms of training, constructivist pedagogy.